Enhancing Science Learning Motivation through Picture Storybooks in Elementary Schools (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
The motivation to learn science among elementary school students in Indonesia remains suboptimal, often hindered by monotonous teaching methods and a lack of engaging learning materials. This study addresses this issue by evaluating the effectiveness of a newly developed science picture storybook intervention designed to enhance student motivation through contextual, narrative-based learning. Unlike conventional textbooks, the storybook embeds scientific concepts within age-appropriate stories accompanied by colorfull illustrations, aiming to foster intrinsic motivation and conceptual understanding. While previous research has validated its practicality and content validity, its effectiveness in improving science motivation had not been empirically tested. This quasi-experimental study involved third-grade students at SD Negeri 5 Mas, Gianyar Regency, Bali (n=17), using a one-group pretest-posttest design. A science motivation questionnaire was administered, and the data were analyzed using paired sample t-tests and normalized gain scores. The findings showed a statistically significant improvement in students’ science learning motivation after using the picture storybook (p < 0.05), with a moderate normalized gain score (g = 0.42). These results highlight the storybook’s moderate yet meaningful impact. The novelty of this intervention lies in its integration of scientific content into culturally relevant narratives to promote engagement and motivation in early science education. The study contributes to the growing field of science education by demonstrating that picture storybooks can serve as an effective motivational tool in elementary classrooms, especially in contexts where motivation is low and student engagement is critical.